A Monte Carlo framework for assessment of how mitigation options affect flood hydrograph characteristics. Issue 1 (2nd January 2016) - Babister, Mark; Retallick, Monique; Loveridge, Melanie; Testoni, Isabelle; Varga, Carlos; Craig, Robert
Abstract: The evolution that is occurring in flood estimation is providing new tools that allow us to better understand the variability of real floods and how to robustly plan large-scale evacuations. The Monte Carlo approach allows design flood estimation inputs to be characterised probabilistically or using an ensemble instead of a single input. While these changes are being used to better estimate design flood levels, they have significant benefit in understanding real flood behaviour by producing thousands of plausible synthetic events. The spatial and temporal variability in rainfall and the timing difference between the key tributaries is modelled. This approach allows impact of management measures to be assessed for all the variability seen in observed events and to properly understand what a mitigation strategy does to average and individual events. This paper discusses the use of Monte Carlo modelling in assessing complex options that are very sensitive to flood characteristics other than the peak flow and compares the results to observed variability of events that cause flood damages. A case study of the Hawkesbury Nepean is discussed.